Irrational medicine use and its associated factors in conflict-affected areas in Mali: a cross-sectional study - Mohamed Ali Ag Ahmed; Alassane Seydou; Issa Coulibaly; Karina Kielmann; Raffaella Ravinetto (Global Health Action)
Background Rational use of essential medicines is a critical step towards prevention and treatment of many illnesses. However, it represents a significant challenge worldwide, and particularly for under-resourced health systems in conflict-affected areas. Objective To assess barriers to rational use of essential medicines at primary healthcare level in conflict-affected areas of Mali. Methods We conducted a cross-sectional study in twenty randomly selected community health centres (CHCs) in four health districts, by applying the World Health Organisation and International Network on Rational Use of Drugs core forms for the rational use of medicines. Seven hundred eighty-nine (789) prescriptions were retrospectively selected and analysed; four hundred forty-three (443) patients were interviewed: and health facility-related indicators were collected prospectively from the 20 CHCs. Results The average number of medicines per prescription was 3.89 ± 1.83; out of these, 94.0% were prescribed by generic name, and 91.0% belonged to Mali’s National List of Essential Medicines. Overall, 68% of the assessed prescriptions included antibiotics; 58% included injectables; and 75.79% were characterized by polypharmacy, i.e. more than two medicines per prescription. In multivariate analysis, the study area and prescriber’s sex were significantly associated with polypharmacy; prescriber’s seniority and training were associated with antibiotic overprescription; the study area, prescriber’s sex and seniority were associated with overprescription of injectables. Moreover, the average price of prescriptions was high in relation to average local income, likely making these unaffordable for many households. Conclusion Excessive polypharmacy and overprescription of antibiotics and injectables undermine the performance of the local health system and the achievement of intended therapeutic outcomes. Our findings provide a solid basis for more targeted and multidisciplinary research, to further inform relevant stakeholders on how best to mitigate the impact of conflict on the rational use of medicines.